1995
DOI: 10.1046/j.1525-1438.1995.05060438.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent for immunotherapy? A study of the immunocompetence of cervical cancer patients

Abstract: Sixty-five patients with cervical carcinoma and 17 control subjects were studied to determine immunocompetence as a prerequisite for immunotherapy using live virus vectors. T-cell immunity, measured by surface phenotype and proliferative assays, was reduced with increasing volume of invasive disease, and independent of treatment effects. Both the CD4+ and CD8+ subsets were affected so that the CD4:8 ratio remained within normal limits. In contrast B-cell number, immunoglobulins and complement were normal as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…This may be the possible reason for the CD4+/CD8+ ratio of CA CX patients not being significantly different as compared to the control group. This result is in good agreement with the work of Fiander et al [19] who have reported that the CD4+/CD8+ ratio does not change in CA CX patients as both the populations are affected [19]. There are, however, previous reports that have shown a reduction in CD4+/CD8+ ratio in PBL of CA CX patients [8–10].…”
Section: Discussionsupporting
confidence: 92%
“…This may be the possible reason for the CD4+/CD8+ ratio of CA CX patients not being significantly different as compared to the control group. This result is in good agreement with the work of Fiander et al [19] who have reported that the CD4+/CD8+ ratio does not change in CA CX patients as both the populations are affected [19]. There are, however, previous reports that have shown a reduction in CD4+/CD8+ ratio in PBL of CA CX patients [8–10].…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, however, the majority of patients with advanced cervical cancer have been heavily pretreated with radiation and/or multiple regimens of palliative chemotherapy and are often profoundly immunocompromised at the time of vaccination treatment (11,19,21). Here, we describe the results of the first clinical trial using recombinant full-length HPV16/18 E7-pulsed autologous DC vaccination as an adjuvant therapy for patients harboring early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of the anti-EGFR antibody (M225) when used as an F(ab) 2 in blocking the growth of tumors in vivo has been previously demonstrated to be only 50% of the activity shown by the intact antibody when it is able to engage the Fc receptors on NK cells [53]. These findings suggest that host factors related to a low number and/or lack of killing activity of effector cells (i.e., NK cells), as previously reported by multiple groups studying the immune-competence of cervical cancer patients heavily pretreated with radiation and chemotherapy, may present a major barrier to the successful clinical development of therapeutic biologic reagents (i.e., IgG 1 mAb such as cetuximab) in end-stage cervical cancer patients [5658]. Prospective evaluation of the immune-competence of such patients therefore seems to be warranted in future studies.…”
Section: Discussionmentioning
confidence: 64%